Thermoluminescence and phototransferred thermoluminescence of tanzanite - Opoku, Kingsley Acheampong (Rhodes University, Faculty of Science, Department of Physics and Electronics)
The thermoluminescence (TL) and phototransferred thermoluminescence (PTTL) properties of tanzanite, an extremely rare gem mineral, have been investigated. While tanzanite shows sensitivity to thermal and optical stimulation of luminescence techniques used for defect probing in insulators, it has received little attention in this regard. A glow curve corresponding to 70 Gy and measured at 1 Â°C s-1 revealed a high intensity peak at 74 Â°C (peak I) and two secondary peaks at 138 and 186 Â°C (peaks II and III). All the peaks exhibit a first order kinetics characteristics, as their positions remained unaffected by changes in either dose or partial heating (ð ‘‡ð ‘š âˆ’ ð ‘‡ð ‘ ð ‘¡ð ‘œð ‘ ). For variable doses from 10 to 200 Gy, the dose response of each peak is sublinear from the analysis of supralinearity indices. Peak I fades at room temperature when readout is delayed following irradiation, and this loss is due to thermal fading. The secondary peaks do not fade. Various methods of kinetic analysis were used to compute the kinetic parameters. For the respective peaks, the activation energy is about 0.84, 1.00 and 1.19 eV. All the peaks suffer thermal quenching with increasing heating rate. Continuous wave optically stimulated luminescence measurements were conducted to supplement the TL analysis with the aim of evaluating the kinetic parameters activation energy of thermal assistance (ð ¸ð ‘Ž) and quenching (ð ›¥ð ¸). The OSL source traps are the same as the TL source traps and occur within 40 to 90 Â°C, 110 to 145 Â°C and 160 to 220 Â°C. The kinetic parameter ð ›¥ð ¸ when luminescence from all the source traps is considered is comparable to that when source traps within 110 to 220 Â°C are measured and does not depend on the dose (10, 50 or 70Gy). Except for irradiation to 10 Gy, ð ¸ð ‘Ž is also comparable. For traps within 160 to 220 Â°C, ð ›¥ð ¸ is comparable for the different doses but higher than that of the other traps, and a similar pattern was observed for ð ¸ð ‘Ž. Measurement of the PTTL signal induced by 470 nm blue LEDs following irradiation to 150 Gy and preheating to 158 Â°C showed that the TL peaks I and II were reproduced under phototransfer. The analysis for order of kinetics and dose response yielded the same results as the convention TL peaks. The model used to describe the PTTL intensity time response profiles shows that the PTTL emanates from a system of one acceptor and three donors, where the latter is a conglomerate of an unknown number of peaks.
Keywords: Thermoluminescence; Thermoluminescence dosimetry; Tanzanite Thermal properties; Dose-response relationship; Thermal fade; Ionizing radiation